Diagnosis of periprosthetic joint infection: The promise of next-generation sequencing - Tarabichi, M; Shohat, N; Goswami, K; Alvand, A; Silibovsky, R; Belden, K; Parvizi, J (Lippincott, Williams & Wilkins, 2018)
Background: Next-generation sequencing is a well-established technique for sequencing of DNA and has recently gained attention in many fields of medicine. Our aim was to evaluate the accuracy of next-generation sequencing in identifying the causative organism(s) in patients with periprosthetic joint infection.